Serum Levels of PYY(1-36) Peptide in Patients with Schizophrenia on Clozapine Monotherapy - Wysokiński, A.; Kowalski, M. L.; Kłoszewska, I. (Pharmacopsychiatry, 2014)
Introduction: The present study was undertaken to determine if patients with schizophrenia on clozapine monotherapy have lower serum levels of peptide YY [PYY(1-36)], which is an endogenous inhibitor of food intake, comparing to healthy controls.Methods: Data for 24 patients (mean age 38.8 years) with paranoid schizophrenia on clozapine monotherapy and 24 healthy subjects (gender- and age-matched; mean age 39.9 years) were analyzed.Results: Fasting serum levels of PYY(1–36) were lower in the clozapine group (178.4±138.4 vs. 277.4±218.1 pg/mL, p=0.034). In the whole study sample PYY(1–36) levels were lower in subjects with body mass index≥25 kg/m2 (p=0.03) and in subjects with abdominal obesity defined using International Diabetes Foundation criteria (p=0.04). There were no significant differences for metabolic syndrome, smoking, impaired fasting glucose, dyslipidemia, and homeostatic model assessment (HOMA) defined insulin resistance.Discussion: Results suggest that weight is associated with levels of PYY. Patients on clozapine had higher body mass index, but not fat mass index or body weight, therefore lower levels of PYY(1–36) in patients taking clozapine may result from clozapine-induced weight gain and central obesity.
Keywords: schizophrenia; clozapine; PYY; metabolic syndrome